Inverted Quantum Dot Light Emitting Diodes using Polyethylenimine ethoxylated modified ZnO - Kim, Hong Hee; Park, Soohyung; Yi, Yeonjin; Son, Dong Ick; Park, Cheolmin; Hwang, Do Kyung; Choi, Won Kook (Nature Publishing Group, 2015)
Colloidal quantum dots (QDs) are an emerging class of new materials due to their unique physical properties. In particular, colloidal QD based light emitting diodes (QDLEDs) have been extensively studied and developed for the next generation displays and solid-state lighting. Among a number of approaches to improve performance of the QDLEDs, the most practical one is optimization of charge transport and charge balance in the recombination region. Here, we suggest a polyethylenimine ethoxylated (PEIE) modified ZnO nanoparticles (NPs) as electron injection and transport layer for inverted structure red CdSe-ZnS based QDLED. The PEIE surface modifier, incorporated on the top of the ZnO NPs film, facilitates the enhancement of both electron injection into the CdSe-ZnS QD emissive layer by lowering the workfunction of ZnO from 3.58 eV to 2.87 eV and charge balance on the QD emitter. As a result, this device exhibits a low turn-on voltage of 2.0–2.5 V and has maximum luminance and current efficiency values of 8600 cd/m2 and current efficiency of 1.53 cd/A, respectively. The same scheme with ZnO NPs/PEIE layer has also been used to successfully fabricate green, blue and white QDLEDs.